PROFIL KERAGAMAN VEGETASI EKOSISTEM MANGROVE DI DESA TAMUKU KABUPATEN LUWU UTARA - Suhendra Purnawan; Subari Yanto; Ernawati S.Kaseng (Jurnal Pendidikan Teknologi Pertanian, 2022)
This study aims to describe the profile of vegetation diversity in the mangrove ecosystem in Tamuku Village, Bone-Bone-Bone District, North Luwu Regency. This research is a qualitative research using survey methods. The data collection technique uses the Quadrant Line Transect Survey technique. The data analysis technique uses the thinking flow which is divided into three stages, namely describing phenomena, classifying them, and seeing how the concepts that emerge are related to each other. The results of this study are the profile of mangrove vegetation in Tamuku Village, which is still found 16 varieties of true mangrove vegetation and 7 varieties of mangrove vegetation joined in the coastal area of Tamuku Village, Bone-Bone District, North Luwu Regency, South Sulawesi. The condition of mangrove vegetation in Tamuku Village is currently very worrying due to human activities that cause damage such as the project of normalization of flow, opening of new farms, disposal of garbage, water pollution due to chemicals, and exploitation of mangrove forests for living needs. The impact is ecosystem damage and reduced vegetation area as a place to grow and develop mangroves.